Successful SCT for Nijmegen breakage syndrome - Albert, Michael; Gennery, A. R.; Greil, Johann; Cale, C. M.; Kalwak, K.; Kondratenko, I.; Mlynarski, W.; Notheis, G.; Führer, M.; Schmid, I.; Belohradsky, B. H. (Bone marrow transplantation, 2010)
Nijmegen breakage syndrome (NBS) is characterized by chromosomal instability, radiation hypersensitivity, characteristic facial appearance, immunodeficiency and strong predisposition to lymphoid malignancy. Traditionally, NBS patients have not undergone hematopoietic SCT (HSCT) owing to concerns about increased toxicity. We therefore report on the HSCT experience in NBS patients in Europe. Six patients were transplanted either for resistant or secondary malignancy (four patients) or severe immunodeficiency (two patients). Five patients received reduced-intensity conditioning regimens. After a median follow-up of 2.2 years, five patients are alive and well. One patient who received myeloablative conditioning died from sepsis before engraftment. Acute GVHD grades I-II occurred in three of five patients, mild chronic GVHD in one. All five surviving patients exhibit restored T-cell immunity. The experience in these six patients suggests that HSCT in NBS is feasible, can correct the immunodeficiency and effectively treat malignancy. Acute toxicity seems to be reasonable with reduced-intensity conditioning regimens.